Implementasi Program Bina Karakter dalam Membangun Akhlak Peserta Didik Kelas XI SMA Muhammadiyah Gayo Lues - Marjuan; Bahtiar Siregar (Islam & Contemporary Issues, 2025)
This study examines the implementation of a character building program in shaping the moral behavior of eleventh-grade students at Muhammadiyah Gayo Lues High School. The research addresses the problem of declining student discipline and social responsibility, which indicates the need for systematic character education grounded in Islamic values. The objective of this study is to analyze the program’s planning, implementation, and its impact on student behavior. A descriptive qualitative method was employed, with data collected through classroom and school observations, in-depth interviews, and documentation. Informants included the principal, vice principal, ISMUBA coordinator, teachers, and purposively selected students. Data were analyzed using the Miles and Huberman interactive model. The findings show that the program is systematically planned through daily, weekly, and monthly activities integrated into school culture. Implementation is supported by consistent teacher role modeling and structured religious and social activities. Behavioral changes were identified through observable indicators, including improved punctuality, compliance with school rules, increased responsibility for assigned tasks, polite communication, and higher participation in collective worship and social service activities. These findings indicate a shift from rule-based compliance to internalized moral awareness, which aligns with the concept of tazkiyatun nafs as value purification reflected in daily behavior. This study contributes an empirical model of Islamic-based character education applicable to senior high schools.